Antioxidant Activity, Total Phenolics, and Total Flavonoids Content of Bajakah Tampala (Spatholobus littoralis): The Indigenous Herbal Medicine from Kalimantan - Mahfudh, Nurkhasanah; Murdi, Habib Basyanur; Utami, Dwi; Ahda, Mustofa; Nashihah, Siti; Andika, Andika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Bajakah tampala (Spatholobus littoralis), a medicinal plant traditionally used in Indonesia, particularly on Kalimantan Island, has garnered interest for its potential health benefits. However, scientific evidence remains scarce. This study investigated the antioxidant activity of S. littoralis extract and its total phenolic and flavonoid content. Ethanol extraction and evaporation were used to prepare the extract. The DPPH method assessed antioxidant activity, while Folin–Ciocalteu and AlCl3 complexation methods quantified total phenolics and flavonoids, respectively. The S. littoralis extract exhibited strong antioxidant activity with an IC50 value of 54.19 ± 8.15 µg/mL. Additionally, the extract contained substantial levels of phenolics (0.649 ± 0.026% GAE) and flavonoids (1.084 ± 0.043% QE). These findings suggest a link between the high phenolic and flavonoid content of S. littoralis extract and its observed strong antioxidant activity.